Refraction correction in precise leveling observations for national leveling network first order - Dimitrov, Nikolay; Georgiev, Ivan; Danchev, Petar (Geodesy and Cartography, 2020)
The paper deals with some problems when applying a correction to reduce the effect of vertical refraction in precise leveling observation. An example for calculating the refraction correction for one first order leveling line with length of 109 km in Bulgaria is given. Comparison between the obtained errors before and after applying refraction correction has been made. The results show that is important to measure the temperatures simultaneously with the leveling by aspiration thermometer with an accuracy of ±0.1 °C. It is recommended to make experimental research and to adopt appropriate for Bulgaria model for taking into account the influence of vertical refraction.